“Nivel de capital social de los emprendimientos que buscan apoyo en el centro de emprendimiento de la universidad técnica de Cotopaxi período febrero-agosto 2021” - Aillon Cuenca, Daysi Estefania (2021)
The present research study aimed to evaluate the level of presence of Social Capital [CS] in entrepreneurships seeking support in the Entrepreneurship Center of the Technical University of Cotopaxi [CEUTC] during the period February-August 2021. The same one is located in the canton Latacunga of the province of Cotopaxi. The research focus is quantitative, descriptive level, and field design. The instrument to measure was used as a survey of social capital in organizations designed by Orkestra - Vasco Institute of Competitiveness. This instrument was applied to a sample of 195 entrepreneurships belonging to the CEUTC. The results showed that the CS level of individual ventures is a little higher than the CS level of the associations, although its variation is not as significant. For both ventures, trust, participation, and reciprocity are difficult aspects to provide. In associations, you have this type of inconvenience because the relationships between individuals of the same association are not beneficial for all. They don´t seek the common good, on the contrary, the benefit is for certain people. This could be one of the factors by which people do not participate in popular and solidarity economy organizations. Finally, the analysis of the indicators of the instrument allowed identifying what happens in the dimensions: information and communication, interests and concerns at work, efficiency, relationships, organizational culture, trust, cooperation, partnership, values, personal attitudes and behaviors, commitment, and social participation.